TINJAUAN YURIDIS PEMBUATAN AKTA PENGGANTI AKTA IKRAR WAKAF TANPA KESEPAKATAN BERSAMA - MUTIA HERLIN SURYANI; ARIEF RAHMAN (Private Law, 2023)
The purpose of this study is to analyze the judge's legal considerations when deciding case Number: 60/Pdt.G/2021/PA.Sub, and analyze the legal protection of waqf land if Nazir has passed away in case Number: 60/Pdt.G/2021/PA.Sub. This type of research is normative research, with the approach method, namely the statute approach, the conceptual approach, and the case approach. The results of the research in case Number: 60/Pdt.G/2021/PA.Sub judge considered that the Defendants did not violence tort law. The making of a deed in lieu of the pledge of waqf land, the waqf has legal protection. The conclusion of the decision Number: 60/Pdt.G/2021/PA.Sub is that the plaintiff is obliged to pay the case administrations and the Defendants have the right to be released from all charges. The suggestion in this research is that land that has been donated or waqf must have a deed immediately for its legal protection.